PENGARUH CORPORATE SOCIAL RESPONSIBILITYTERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING PADA PT. ANGKASA PURA I (PERSERO) BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI-BALI - I Nyoman Gede Arya Diatmika (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
The purpose of this study was to determine: (1) Effect of Corporate Social Responsibility (CSR) to corporate value, (2) Influence of Corporate Social Responsibility (CSR) to the value of the company to profitability as moderating variable. The method used was a causal comparative research. Data used in this study are primary and secondary data, namely quantitative data. The method of analysis in this research was simple regression analysis and regression. The results of this study indicated that: (1) Corporate Social Responsibility (CSR) had positive and significant impact on the value of the company, (2) profitability as a moderating variable could not moderate the influence of Corporate Social Responsibility (CSR) to corporate value.